2022
DOI: 10.1177/10556656221078744
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery After Cleft Lip Repair: Protocol Development and Implementation in Outreach Settings

Abstract: Introduction Clefts of the lip are of the most common congenital craniofacial anomalies. The development and implementation of an enhanced recovery after surgery (ERAS) protocol among patients undergoing cleft lip repair may decrease postoperative complications, accelerate recovery, and result in earlier postoperative discharge. Methods A modified ERAS program was developed and applied through Global Smile Foundation outreach craniofacial programs. The main components of this protocol include: (1) preoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…This finding aligns with the ERAS goal of reducing postoperative pain by multimodal, non-opioid management. 14 Findings were also consistent among procedure types that we examined. Despite ERAS implementation, patients still required a comparable amount of morphine in both cohorts across the whole study timeframe, although the average is down trending.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This finding aligns with the ERAS goal of reducing postoperative pain by multimodal, non-opioid management. 14 Findings were also consistent among procedure types that we examined. Despite ERAS implementation, patients still required a comparable amount of morphine in both cohorts across the whole study timeframe, although the average is down trending.…”
Section: Discussionsupporting
confidence: 53%
“…2 More recently, ERAS protocols for cleft lip repair have been proven to reduce opioid use, leading to shortened time to feeding resumption and return to function. 14,16,22 Our study sought to identify the benefits that an ERAS protocol with oral acetaminophen had in the immediate 2 years following its implementation compared to the 2 years prior. By implementing ERAS, an expected rise in both IV and PO NSAID utilization for pain management was witnessed during the patient's hospital course.…”
Section: Discussionmentioning
confidence: 99%
“…10 GSF and Smile Train have developed quality assurance and anesthetic guidelines to prioritize and ensure patient safety in international surgical endeavors. [34][35][36] In a similar way, protocols can be developed that outline best practices for maximizing follow-up. This protocol could outline the way future appointments are discussed during initial visits, recommend ways for the local providers to maintain continuity with patients throughout the year, and detail what information is given to patients.…”
Section: Follow-up Rates and Protocol Developmentmentioning
confidence: 99%
“…However, there is no proven benefit to longer courses of postoperative antibiotics in ‘clean contaminated’ surgeries such as UCLR [8]. In a 2022 ERAS protocol implemented in outreach settings through the Global Smile Foundation, intravenous antibiotics were administered at the time of incision usually with a first- or second-generation cephalosporin [9 ▪ ]. This was followed by 5 days of an equivalent oral antibiotic along with topical antibiotic ointment application [9 ▪ ].…”
Section: Introductionmentioning
confidence: 99%
“…In a 2022 ERAS protocol implemented in outreach settings through the Global Smile Foundation, intravenous antibiotics were administered at the time of incision usually with a first- or second-generation cephalosporin [9 ▪ ]. This was followed by 5 days of an equivalent oral antibiotic along with topical antibiotic ointment application [9 ▪ ]. Of the 126 patients operated on in the study, there were no reported immediate postoperative complications, including infection or wound dehiscence, however the authors reported three patients had delayed wound healing [9 ▪ ].…”
Section: Introductionmentioning
confidence: 99%